Self-reported intake of high-fat and high-sugar diet is not associated with cognitive stability and flexibility in healthy men. (1st April 2023) - Hartmann, Hendrik; Janssen, Lieneke K.; Herzog, Nadine; Morys, Filip; Fängström, Daniel; Fallon, Sean J.; Horstmann, Annette
Abstract: Animal studies indicate that a high-fat/high-sugar diet (HFS) can change dopamine signal transmission in the brain, which could promote maladaptive behavior and decision-making. Such diet-induced changes may also explain observed alterations in the dopamine system in human obesity. Genetic variants that modulate dopamine transmission have been proposed to render some individuals more prone to potential effects of HFS. The objective of this study was to investigate the association of HFS with dopamine-dependent cognition in humans and how genetic variations might modulate this potential association. Using a questionnaire assessing the self-reported consumption of high-fat/high-sugar foods, we investigated the association with diet by recruiting healthy young men that fall into the lower or upper end of that questionnaire (low fat/sugar group: LFS, n = 45; high fat/sugar group: HFS, n = 41) and explored the interaction of fat and sugar consumption with COMT Val 158 Met and Taq1A genotype. During functional magnetic resonance imaging (fMRI) scanning, male participants performed a working memory (WM) task that probes distractor-resistance and updating of WM representations. Logistic and linear regression models revealed no significant difference in WM performance between the two diet groups, nor an interaction with COMT Val 158 Met or Taq1A genotype. Neural activation in task-related brain areas also did not differ between diet groups. Independent of diet group, higher BMI was associated with lower overall accuracy on the WM task. This cross-sectional study does not provide evidence for diet-related differences in WM stability and flexibility in men, nor for a predisposition of COMT Val 158 Met or Taq1A genotype to the hypothesized detrimental effects of an HFS diet. Previously reported associations of BMI with WM seem to be independent of HFS intake in our male study sample.